The travelers' Charleston : accounts of Charleston and lowcountry South Carolina, 1666-1861 - Fant, Jennie Holton (University of South Carolina Press, 2016)
The Travelers' Charleston is an innovative collection of firsthand narratives that document the history of the South Carolina Lowcountry region, specifically the Charleston area, from 1666 until the start of the Civil War. Jennie Holton Fant has compiled and edited a rich and comprehensive history as seen through the eyes of writers from outside the South. She provides a selection of unique texts that include the travelogues, travel narratives, letters, and memoirs of a diverse array of travelers who described the region over time. Further Fant has mined her material not only for validity but to identify any people her travelers encounter or events they describe. She augments her resources with copious annotations and provides a wealth of information that enhances the significance of the texts. The Travelers' Charleston begins with explorer Joseph Woory's account of the Carolina coast four years before the founding of Charles Town and concludes as Anna Brackett, a Charleston schoolteacher from Boston, witnesses the start of the Civil War. The volume includes Josiah Quincy Jr.'s original 1773 journal; the previously unpublished letters of Samuel F.B. Morse, a portrait artist in Charleston between 1818 and 1820; the original letters of Scottish aristocrat and traveler Margaret Hunter Hall (1824); and a compilation of the letters of William Makepeace Thackeray written in Charleston during his famous lecture tours in the 1850s. Using these sources, combined with excepts from other carefully chosen travel accounts, Fant provides an unusual and authoritative documentary record of Charleston and the Lowcountry that allows the reader to step back in time and observe a bygone society, culture, and politics to note key characters and hear them talk and to view firsthand the history of one of the country's most distinctive regions.